Ultra-wideband side-lobe level suppression using amplitude-adjustable metasurfaces. (10th December 2018) - Zheng, Qiqi; Li, Yongfeng; Han, Yajuan; Jing, Yao; Feng, Maochang; Pang, Yongqiang; Wang, Jiafu; Ma, Hua; Qu, Shaobo; Zhang, Jieqiu
Abstract: An amplitude-adjustable metasurface has been proposed to suppress the side-lobe level over an extra-wide frequency band. A polarization-selective unit cell is designed to constitute the metasurface, which can manipulate the amplitudes of the co-polarization reflection coefficients and cross-polarization transmission coefficients, while the phases remain unchanged. The amplitude of the metasurfaces is discretely Taylor-distributed. For example, two metasurfaces were designed to achieve side-lobe level suppression (SLLS), of reflected and transmitted beams, respectively. The simulations demonstrated that two metasurfaces have good performance on SLLS of reflected/transmitted beams, with approximately −20 dB SLL in a wide frequency region. It is expected that the designed amplitude-adjusted metasurfaces may find potential application in antennas and stealth techniques.